BREAST FEEDING SUPPORT IN PREMATURE INFANTS: PROBLEMS AND SOLUTIONS - I. A. Belyaeva; T. V. Turti; O. L. Lukoyanova; M. I. Ivardava; E. O. Tarzyan (Педиатрическая фармакология, 2014)
Support of long-term breast feeding is a pressing issue of neonatology. It is known that the unique composition of breast milk ensures proper physical and neuropsychic development of infants, as it contains all the necessary nutrients in the sufficient amount and optimal proportion. The authors gave specific attention to provision of premature infants, especially with very low and extremely low birth weight, with breast milk. However, it is very difficult to launch and maintain breast feeding in this very category of patients. There are many reasons impeding adequate provision of premature infants with breast milk. The main problem on the part of the mother is hypogalactia, which may be caused by preterm labor stress, lack of confidence in successful lactation, temporary medical contraindications and, therefore, deviant formation of the lactation dominant, motivation towards prolonged breast feeding etc. On the part of the child: severe condition, no or weak sucking reflex, often — prolonged parenteral and tube feeding, need in supplementary feeding. The article presents published data on various methods of maintaining breast feeding at the stage of hospital developmental care of premature infants and experience of breast feeding support accumulated at the Scientific Center of Children’s Health, which proves that simultaneous support and follow-up of the child’s mother and her family in whole by several specialists (neonatologist/pediatrician, psychologist, breast physician, dietician and recreation therapist) not only at the stages of labor and development care, but also after discharge from hospital are required to ensure rational and prolonged breast feeding of premature infants and normal growth and development thereof.